Development of low cost autonomous wheelchair using gps for outdoor purposes - Salma, Yaakub (2021)
Electric wheelchair has been widely used to facilitate and minimize the user’s effort to move independently. Users prefer to control the movement of the wheelchair on their own without any assistance. Although electric wheelchairs are considered a good solution to minimise the effort in independently moving the wheelchair, but unfortunately, electric wheelchairs are expensive in Malaysia. Moreover, most of the available electric wheelchairs in the market use only the joystick as control device. However, the joystick is not suitable for most cases. For example, blind users, users with mental disorders or with both hands paralyzed, are unable to hold and control the joystick. Such users still need to be assisted by others. However, other people will not always be available to help due to any constraints. Using other means of control devices may partially solve the issues but may not be entirely resolved. Therefore, wheelchair needs some improvement utilising smarter and low cost control system that can resolve some critical cases for example the users that are unable to use both their hands and legs. This research main focuses on developing a control system to allow wheelchairs to move autonomously from one point to another using Global Positioning System (GPS) while saving the cost to make it affordable for the users. The main problem in building an autonomous system is the accuracy and consistency of GPS reading. To solve that problem a simple algorithm is developed to improve the accuracy in positioning and path planning for the wheelchair. The averaging technique was applied in positioning to improve the accuracy and consistency of the GPS reading. The GPS positioning becomes more accurate as the averaging technique reduced the GPS reading to two consistent readings instead of five different readings. In terms of accuracy, the distance between the actual point and the GPS measured point had decreased from 4 meters to only 3 meters. The stop angle was adjusted by changing the setting for the stop angle’s constant because the wheelchair does not immediately stop at the desired turning point due to the Law of Inertia. The value of that constant has to be experimentally set according to error in turning angle. The suggested solution is by integrating rotary encoder with the compass. The constant kp= 60 pulses was applied in straight movement correction, and can be seen that the wheels always trying to balance each other. Experiments have been conducted to test the ability of the system and fulfil the task of reaching a pre-stated destination accurately. This wheelchair can be used for outdoor movement as the GPS is more accurate outside of the building. For instance, the users want to go to the nearest clinic or park within 1 kilometre from their home. This will save time as they don’t need to wait to seek for assistance.